Retrocaval Ureter: A Study of 13 Cases - Yarmohammadi, Aliasghar; Mohamadzadeh Rezaei, Mohamadali; Feizzadeh, Behzad; Ahmadnia, Hassan (Urology Journal, 2009)
Introduction: The aim of this study was to report our 23-year experience in the diagnosis and treatment of retrocaval ureter. Materials and Methods: Data from 13 patients with retrocaval ureter were reviewed. Intravenous urography and retrograde pyelography had been used for confirming the diagnosis. All of the patients had been symptomatic and undergone surgery. A control intravenous urography had been performed 6 months postoperatively. Results: The mean age of the patients was 23 years (range, 12 to 37 years). Twelve patients (92.3%) were men. The clinical manifestations were pyelonephritis in 7 (53.8%), right flank pain in 4 (30.8%), gross hematuria in 1 (7.7%), and ureteral calculus in 1 (7.7%). All of the patients had type 1 right-sided retrocaval ureter. Associated anomalies were seen in none of the patients. The control intravenous urography showed improvement of renal function. Conclusion: In our patients, the most common cause of referral was pyelonephritis. In symptomatic cases, operation is needed and can improve renal function.